Sukuk Negara as an Alternative for APBN Financing in Indonesia - Riswan Riswan; Andi Rustam; Linda Arisanty Razak; Muchriana Muchran (Penerbit Goodwood, 2023)
Purpose: In supporting Anggaran Pendapatan dan Belanja Negara (APBN) financing, the government always prioritizes non-debt financing. However, the government also uses debt financing to meet the financing needs of the state budget. One of the alternative efforts that must be made by the Government is to develop Sharia-based on Surat Berharga Negara (SBN) or what can be called Sukuk Negara. Research Methodology: This research uses a qualitative methodology. Results: Based on the results of research that has been conducted, it is known that State Sukuk have a major role in driving the growth of Islamic finance in Indonesia and can reduce the financing of the state budget deficit. Conclusions: State Sukuk play an important role as an alternative sharia-based financing instrument to support APBN financing and reduce dependence on conventional debt financing. Limitations: This study is limited by its qualitative approach and relies mainly on secondary data, so it does not provide empirical measurement of the direct impact of State Sukuk on APBN deficit financing. Contributions: This study contributes to the literature on Islamic public finance by highlighting the strategic role of State Sukuk in strengthening Islamic finance and supporting sustainable state budget financing.